Tree-ring distinctness, dating potential and climatic sensitivity of laurel forest tree species in Tenerife Island - García López, María Auxiliadora; Rozas Ortiz, Vicente Fernando; Olano Mendoza, José Miguel; Sangüesa Barreda, Gabriel; García Hidalgo, Miguel; Gómez González, Susana; López Rubio, Roberto; Fernández Palacios, José M.; García González, Ignacio; García-Cervigón Morales, Ana Isabel (Dendrochronologia, 2022)
Producción Científica Macaronesian laurel forests are the only remnants of a subtropical palaeoecosystem dominant during the Tertiary in Europe and northern Africa. These biodiverse ecosystems are restricted to cloudy and temperate insular environments in the North Atlantic Ocean. Due to their reduced distribution area, these forests are particularly vulnerable to anthropogenic disturbances and changes in climatic conditions. The assessment of laurel forest trees’ response to climate variation by dendrochronological methods is limited because it was assumed that the lack of marked seasonality would prevent the formation of distinct annual tree rings. The aims of this study were to identify the presence of annual growth rings and to assess the dendrochronological potential of the most representative tree species from laurel forests in Tenerife, Canary Islands. We sampled increment cores from 498 trees of 12 species in two well-preserved forests in Tenerife Island. We evaluated tree-ring boundary distinctness, dating potential, and sensitivity of tree-ring growth to climate and, particularly, to drought occurrence. Eight species showed clear tree-ring boundaries, but synchronic annual tree rings and robust tree-ring chronologies were only obtained for Laurus novocanariensis, Ilex perado subsp. platyphylla, Persea indica and Picconia excelsa, a third of the studied species. Tree-ring width depended on water balance and drought occurrence, showing sharp reductions in growth in the face of decreased water availability, a response that was consistent among species and sites. Inter-annual tree-ring width variation was directly dependent on rainfall input in the humid period, from previous October to current April. The four negative pointer years 1995, 1999, 2008 and 2012 corresponded to severe drought events in the study area. This study gives the first assessment of dendrochronological potential and tree-ring climate sensitivity of tree species from the Tenerife laurel forest, which opens new research avenues for ...